A faithful man [videorecording (DVD)] - Garrel, Louis; Garrel, Louis; Garrel, Louis; Casta, Laetitia, 1978-; Depp, Lily-Rose, 1999-; Engel, Joseph (Kino Lorber, 2019)
A hapless journalist gets back together with his former girlfriend, who eight years ago married his best friend and is now a widow, but their relationships become complicated when his friend's sister suddenly announces that she has been in love with him for years and the girlfriend's son claims that his mom killed his dad.